The Discoursive Perspective Of Liberalism Versus Multiculturalism - Otto Gusti Ndegong Madung; Winibaldus Stefanus Mere (International Journal of Indonesian Philosophy & Theology, 2022)
This paper aims to show the limitations of the liberal viewpoint vis-à-vis overcoming the conflict between freedom of religion and belief in Indonesia. The multi-ethnic and multi-religious condition, a unique feature of Indonesian society, demonstrates that the conventional liberal framework of the concept of freedom of religion and belief is insufficient. To complete this article, the writer employs the literature research method. This research can formulate many findings: freedom of religion and belief is not only concerned with the individual. And an individual right to choose his/her faith is strongly linked to how one legitimately expresses oneself in communities based on ethnicity and/or religion. Furthermore, plurality in a multicultural society presumes acknowledging a fundamental truth that can be expressed in many ways.